Development of Chemistry in Context E-book on Chemistry Subject Grade XI of Senior High School for Facing Literacy and Numerical Competency Assessment - Salsabila, Elfina; Sari, Rr. Lis Permana (Jurnal Pendidikan Matematika dan Sains, 2024)
This research aimed to develop an e-book titled "Chemistry in Context" for Grade XI Senior High School students. The study assessed the e-book's quality across nine aspects: conceptual accuracy in chemistry and science, relevance of chemistry in discourse, content material, construction of questions, language and cultural appropriateness, e-book design, usability instructions, literacy components, and numerical aspects. The development process followed the 4D Model, encompassing Define, Design, Develop, and Disseminate stages.The outcome of this research is a comprehensive e-book comprising 30 discourse units and Minimum Competency Assessment questions designed to enhance literacy and numerical skills among Grade XI students. Evaluation by reviewers yielded an average score of 182 out of a maximum of 205 points, translating to an impressive 88.78% rating, indicating the e-book's high suitability for educational use.